A study of Public Cloud Risks at companies in UAE - ALLAMADANI, NIDAL (2017)
In the modern age, technology changed the way of conducting business and transfers the world into a global village. By clicking few mouse buttons, any person can reach worldwide market in any area in the world. Public cloud computing technologies help companies to adopt ICT and use it effectively. Multiple researches have been carried out on the risks of adopting public cloud by companies in both developed and developing countries. The adoption of Public Cloud Computing by companies is hindered due to the risks involved in cloud computing, it is vital to analyse the perspective of people from different organisations. This research aims to provide Business and Organisations in U.A.E with a clear overview of different perspective on the risks involved in the adoption of cloud computing. This research is one of a kind conducted in U.A.E, providing clear perspective of people with the adoption or rejection of public cloud computing highlighting the concerns pertaining to various Risks. Companies and Big Organisations can use this to further enhance their mode of operations and formulated solutions to overcome various risks associated with the adoption of public cloud computing. The findings have been collected from studies from a specific country or region may not be applied or compatible with other countries in the world, because the economic development and geopolitical are different from country to other country. UAE (United Arab Emirates) is a developed country, and by its unique fast development in almost all areas (especially information technology field) is not like other country or area in the world. Hence, no researches implemented outside UAE’s borders can be truly adopted in UAE. This study showed the levels of perceiving risks of employees, who are working in UAE companies in UAE to adopting public cloud computing as a business strategy. The study carries out a positivist philosophy, supported by quantitative methodology, where questionnaires have been sent to different people, who are working in UAE companies, to respond to the research questions. The collected data have been analysed using SPSS and Excel. Findings of the descriptive analysis show that employees have high overall perceived risk. T-tests and One Way ANOVA were used to compare the means of overall perceived risks between different groups. The key findings in this study project light the perception of overall risk in IT industry and the one with the demographics of a company. Hence experience in the IT field and working in IT department have been found as the only personal factors that can affect perception of overall risk associated with PC services. On the other hand, out of the company characteristics investigated, it was found that number of PC services used in the company and type of branch were the only factors affecting perception of overall risk associated with Public Cloud.